2018
DOI: 10.18046/j.estger.2018.146.2810
|View full text |Cite
|
Sign up to set email alerts
|

Emprendimiento de negocios propios en el Perú: el rol de los factores sociodemográficos personales a nivel de departamentos

Abstract: El artículo tiene como objetivo especificar las variables sociodemográficas pertenecientes al individuo que determinan la creación de negocios propios en los departamentos del Perú. Para ello, con información de la Encuesta Nacional de Hogares sobre Condiciones de Vida y Pobreza (ENAHO) del año 2015, se efectúan regresiones econométricas de un modelo probit para cada uno de los 24 departamentos. Los resultados indican que las principales características sociodemográficas que determinan la probabilidad de estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
3
7
0
10
Order By: Relevance
“…Likewise, it is observed that the probability of being at level 2 (starting the business or already having it in operation), is higher if it is a man (42.90% compared to 32.30% of women), which is in line with what is reported in the literature, which shows greater participation of men in contexts of entrepreneurship (Diaz et al, 2010). Concerning marital status, the probability of being at level 2 of the enterprise is lower if he is single (32.10% compared to 46.20% for a situation other than single), a situation that also coincides with that expressed by León Mendoza (2018), mentioning the possibility of having better conditions and support from the spouse to undertake.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Likewise, it is observed that the probability of being at level 2 (starting the business or already having it in operation), is higher if it is a man (42.90% compared to 32.30% of women), which is in line with what is reported in the literature, which shows greater participation of men in contexts of entrepreneurship (Diaz et al, 2010). Concerning marital status, the probability of being at level 2 of the enterprise is lower if he is single (32.10% compared to 46.20% for a situation other than single), a situation that also coincides with that expressed by León Mendoza (2018), mentioning the possibility of having better conditions and support from the spouse to undertake.…”
Section: Resultssupporting
confidence: 60%
“…Reports have been made on the incidence of sociodemographic factors on the business intentions of graduate students (Tarapuez, Aristizábal, et al, 2018), especially personal sociodemographic factors, in addition to requiring the entrepreneur to possess skills and motivations that are considered to be explanatory when it comes to entrepreneurship (León Mendoza, 2018) and that influence the entrepreneurial activity of young people either out of necessity or opportunity (Canales, Román, & Ovando, 2017).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the aspects that relate entrepreneurial activity with socioeconomic factors are variables such as gender, age, educational level, income [54][55][56][57][58][59], marital status, and socioeconomic stratum [60,61]; as well as parental education and family environment [62,63]. Taking into account the above, it is important to describe the findings related in the literature, around the mentioned sociodemographic variables that affect entrepreneurial activity [55].…”
Section: Introductionmentioning
confidence: 99%